MANAGEMENT OF ELECTRONIC RESOURCES FOR EFFECTIVE LIBRARY SERVICES IN FESTUS AGHAGBO NWAKO LIBRARY, NNAMDI AZIKIWE UNIVERSITY, AWKA (NAU Journal of Library and Information Science, 2018)
This paper discussed the management of e-resources for effective library services in Festus Aghagbo Nwako (FAN) Library of Nnamdi Azikiwe University, Awka. The paper x-rayed the activities of e-resource generation and use in the Nnamdi Azikiwe University community and the management practices of these resources. The e-library content, services, e-management construct challenges in the management of e-resources as well as in FANLwere highlighted. The paper concluded that both the library and the University management should give more attention to the provision and management of e-resources, bearing in mind the peculiarity of its effectiveness in information delivery. Part of the recommendation is that continuous acquisition of e-resources in the University library should form part of the acquisition policy of FAN Library.
Keywords: Festus Aghagbo Nwako Library; Generating e-resources; Use of e-resources; e-resources Construct; Effective Library Services